Service‐level agreement aggregation for quality of service‐aware federated cloud networking. Issue 5 (1st September 2015) - Stanik, Alexander; Koerner, Marc; Kao, Odej
Abstract : Since the cloud paradigm becomes increasingly popular for dynamic resources allocation, the flexibility of a cloud is still limited regarding network services and their autonomous federation between different providers. The following architectural approach introduces a generic layered model to orchestrate and federate heterogeneous networks. In particular, an architecture is presented that enables quality of service (QoS) aware parameterisation of network resources in a cloud infrastructure of a single data‐centre as well as for a federation. Furthermore, this architecture uses a service‐level agreement (SLA) protocol and language to expose key performance indicators and to negotiate appropriate QoS constrains that are applied to the virtually sliced underlying network substrate. In this way, capabilities of the orchestration and the current utilisation of the network are building the foundation for dynamic negotiated SLAs and the within‐guaranteed QoS network resources. Therefore an aggregation mechanism is illustrated for merging service‐level objectives and for guaranteeing a single SLA that specifies obligations and responsibilities of all participants.